Impeded nursing care: nurses' lived experiences - Drury, John (Curtin University, 2001)
This phenomenological study describes the lived experience of ten registered nurses who provided a standard of nursing care that they perceived to be impeded because of their negative reactions to their patient's condition. Purposeful sampling was used to recruit participants via an advertisement in a local nursing organisation's newsletter. In-depth interviews generated data about the nurses' personal and professional experiences. Data analysis incorporated the qualitative methods of Huserrlian (descriptive) phenomenology and Colaizzi's method of data analysis. Findings revealed that during some stage of the nurses' careers they had reacted negatively to a patient's condition. These negative reactions included frustration, annoyance, nurses fearing for their own safety, revulsion, sadness and feelings of guilt that impeded care had been provided. These reactions translated into behaviours that were associated with providing nursing care to the patient that the nurses themselves perceived to be of impeded quality. Behaviours included not being there or spending less time with the patient, not communicating well and having less rapport with the patient, not meeting the patient's psychological and social needs and not meeting the patient's spiritual needs. The nurses found their awareness that this had occurred disturbing and they devised strategies to cope personally and also to ensure that a better quality of care was provided in subsequent situations. Strategies included discussions with colleagues, arranging for colleagues to provide care for the patient, mental preparation, and using individual coping strategies.There was a pattern of contextual factors impeding the provision of good care. These factors included an existing poor rapport with the patient, a bad experience with a patient with similar characteristics, time pressures and a lack of autonomy, chronic work stress, low staffing levels, a lack of clinical experience, negative reactions to the patient's condition by other staff members, a lack of visits by the patient's significant others and disagreement with the patient's medical treatment.